Universiti Malaysia Pahang- first Technical University in Malaysia to achieve 5-Star QS rating - Irene, Wei Kiong Ting (2018)
On 17 July 2018, faculty and staff at Universiti Malaysia Pahang (UMP) cried “hurray!” for being awarded the prestigious QS 5-star overall rating. We shouted for joy as becoming the only and first Malaysian technical university and non-research university to have received such a distinguished 5-star overall excellence rating. Specifically, UMP’s QS Star ratings reflect high qualities of teaching, research, and community services taking place at the institution, all of which contribute towards the great program strength and high employability generated. UMP also does well in the advanced criteria of QS Star ratings, namely ‘Innovation’ and ‘Inclusiveness’, with 5-star ratings. This groundbreaking achievement reinforces the results of previous prestigious ratings and high-profile assessments. Big congratulations to UMP!